2021
DOI: 10.1186/s12954-021-00555-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-beverage alcohol consumption among individuals experiencing chronic homelessness in Edmonton, Canada: a cross-sectional study

Abstract: Background Among individuals experiencing homelessness, the prevalence of alcohol use disorder is extremely high. Alcohol-related harms are compounded by the use of non-beverage alcohol (NBA; e.g. rubbing alcohol, cooking wine). The dangers of NBA consumption pose significant risks to the individual and to others when consumed in large quantities and when mixed with other substances. The objectives of this paper are to describe the alcohol consumption patterns of individuals experiencing homele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The frequent use of non-beverage alcohol—a substance both affordable and accessible—by people who experience homelessness has been extensively reported in the literature (e.g., [ 19 , 21 , 76 ]). In Canada, its consumption is widespread among these populations and its harmful effects, a matter of concern [ 7 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The frequent use of non-beverage alcohol—a substance both affordable and accessible—by people who experience homelessness has been extensively reported in the literature (e.g., [ 19 , 21 , 76 ]). In Canada, its consumption is widespread among these populations and its harmful effects, a matter of concern [ 7 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our review found several potential health- and harm reduction-related benefits of MAPs, including improved quality of life, reduced alcohol consumption particularly with decreased NBA use (particularly for programs with Stringent outside drinking policies compared to Lax), less hazardous consumption patterns, and potential stabilizations in biological markers of alcohol use during MAP participation. Decreased consumption of both beverage alcohol and NBA has several downstream benefits, including fewer traumas, assaults, seizures, hazards from NBA including ethanol, higher alcohol content, and additive ingredients [ 77 ], and effects of acute intoxication. Potential harms of continued alcohol consumption that are not yet represented in the MAP literature include the progression of liver disease and cirrhosis, cancer, hypertension, or cardiac disease [ 1 , 7 , 78 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this research has identi ed the incidences of heavy alcohol use and binge drinking patterns, particularly among runaway and street youth (May eld Arnold et al, 2012; Nyamathi et al, 2012;Smart et al, 1994). These studies have also reported the prevalence of non-beverage alcohol drinking among people experiencing homelessness when they cannot afford regular alcohol (Erickson et al, 2018;Ezard et al, 2018;Podymow et al, 2006;Stockwell et al, 2018;Westenberg et al, 2021). However, to our knowledge few studies (Stockwell et al, 2013) have examined how the social contexts in which these persons drink constitute a signi cant source of harm and shape their drinking patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its affordability and accessibility the frequent use of non-beverage alcohol among people who experience homelessness has been extensively reported in the literature (e.g., Egbert et al, 1985;Erickson et al, 2018;Westenberg et al, 2021). However, most participants indicated that they did not drink this type of alcohol.…”
Section: Non-beverage Alcohol Drinkingmentioning
confidence: 99%
See 1 more Smart Citation